Security treats of computerized banking systems (CBS): The Managers' perception in Malaysia - Malami, Abu Bakar; Zainol, Zaini; Puat Nelson, Sherliza (2012)
Internal control system is an important pillar in an organisation. Considering the evidence from major accounting fraud cases that occurred consequence to weak internal control, such as Enron, it could also occur in a financial institution. Hence, the objective of this study is to investigate the bank managers’ opinion on the likelihood of security threats in the computerised banking systems (CBS) in Malaysia. Since most major financial institutions operate in the capital city of Kuala Lumpur, questionnaires were sent to almost all bank branches in Kuala Lumpur. The findings are expected to provide a platform for bank managers to share their threats’ experience. Secondly, to assist them in designing and formulating a sound and effective internal control system that will provide reasonable assurance for achieving the bank’s mission. Findings are also expected to provide general insights of internal control system, as most information is very remote and confidential, thus generate a platform for promoting an efficient and effective internal control practice in financial institutions.